2009
DOI: 10.1111/j.1432-2277.2009.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-free immunosuppression in liver transplantation: a meta-analysis and meta-regression of outcomes

Abstract: To examine the impact of steroid withdrawal from the immunosuppression protocols in liver transplantation. The electronic databases Medline, Embase, Pubmed and the Cochrane Library were searched. Meta‐analysis pooled the effects of outcomes of a total of 2590 patients enrolled into 21 randomized controlled trials (RCTs), using classic and modern meta‐analytic methods. Meta‐analysis of RCTs addressing patients transplanted for any indication showed no differences between corticosteroid‐free immunosuppression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 32 publications
(81 reference statements)
4
60
3
1
Order By: Relevance
“…A more recent meta-analysis [56] evaluated steroid withdrawal in LT for any indication in 2590 patients from 21 RCT. There were no differences between Cs-free and Cs-based protocols in nearly all analyzed outcomes.…”
Section: Steroid Avoidancementioning
confidence: 99%
“…A more recent meta-analysis [56] evaluated steroid withdrawal in LT for any indication in 2590 patients from 21 RCT. There were no differences between Cs-free and Cs-based protocols in nearly all analyzed outcomes.…”
Section: Steroid Avoidancementioning
confidence: 99%
“…However, two recent meta-analyses found that steroid-free immunosuppression protocols are significantly better and provide benefits related with such factors as the acute graft hepatitis, HCV recurrence, cholesterol levels and the development of de novo diabetes mellitus (Sgourakis et al, 2009, Segev et al, 2008. Thus, the use of steroid-free immunosuppression protocols improves the management of metabolic complications.…”
Section: Role Of Immunosuppression In Recurrence Of Hepatitis Cmentioning
confidence: 99%
“…The majority of IS protocols in the initial months after liver transplantation involve the use of steroids. Dosage and tapering schedules vary between transplant institutions and as a consequence makes it difficult to come to a clear conclusion of the importance of steroids in HCC recurrence (38). Nevertheless, there is some data that suggests the use of steroids might increase the recurrence in this setting (39).…”
Section: Steroidsmentioning
confidence: 99%